2021
DOI: 10.1002/chem.202004205
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Synthesis of Hierarchical Yolk/Double‐Shelled SiOx@TiO2@C Nanospheres for High‐Performance Lithium‐Ion Batteries

Abstract: Invited for the cover of this issue is Qinghua Gong, Guowei Zhou, and co‐workers at Qilu University of Technology. The dial represents the etching time of SiOx yolk in NaOH solution and the brightness of the Chinese red lantern represents the electrochemical performance of the composites. Read the full text of the article at 10.1002/chem.202003246.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…25−27 As a result, a double-shell design with both carbon and TiO 2 components has been put forward. 6,28 A recent report showed the preparation of Sb@C@ TiO 2 triple-shell nanoboxes, and they exhibited an enhanced sodium storage performance, better than that of the Sb@C boxin-box structures. 6 Another recent report presented that yolk/ double-shelled SiO x @TiO 2 @C nanospheres have an outstanding lithium-ion battery performance.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25−27 As a result, a double-shell design with both carbon and TiO 2 components has been put forward. 6,28 A recent report showed the preparation of Sb@C@ TiO 2 triple-shell nanoboxes, and they exhibited an enhanced sodium storage performance, better than that of the Sb@C boxin-box structures. 6 Another recent report presented that yolk/ double-shelled SiO x @TiO 2 @C nanospheres have an outstanding lithium-ion battery performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 Another recent report presented that yolk/ double-shelled SiO x @TiO 2 @C nanospheres have an outstanding lithium-ion battery performance. 28 For the Sb 2 S 3 materials, there have been no reports on a double-shell design, but there has been a study on the Sb 2 S 3 /TiO 2 /C composite, which shows better lithium storage properties in comparison to the Sb 2 S 3 /C electrode in the half cells or full cells. 29 Herein, a unique double-shelled Sb 2 S 3 /Sb@TiO 2 @C nanorod composite has been designed layer-by-layer; the Sb 2 S 3 nanorod precursors are first prepared and applied as templates, then a TiO 2 middle layer is subsequently coated on the surface of Sb 2 S 3 nanorods after the hydrolysis of tetrabutyl titanate, and the final product is obtained by carbonization of the polydopamine (PDA) coating on Sb 2 S 3 @TiO 2 @PDA nanorod intermediates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, TiO 2 has become promising alternative anode materials for high-safety LIBs. However, the poor conductivity of TiO 2 causes the large initial impedance of TiO 2 anode, which seriously affects its rate performance [6][7][8][9]. In order to solve the inherent defect, different methods have been tried in recent years, including reducing particle size, doping elements, carbon coating, designing nanostructure morphology and introducing defects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the rapid development of core–shell engineering in catalysis, electronics, photoluminescence and biomedicine field [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ], the application of core–shell techniques in energetic materials has had a slow start. There are two major problems responsible for this; one is that the sensitivity and mechanically fragile nature of energetic crystals increase the process handling difficulty, the other is that the smooth and chemically inert surface of explosive particles leads to the weak interfacial interactions between particles [ 30 , 31 , 32 ]. Fortunately, recent developments in core–shell engineering have significantly enhanced our understanding of the formation mechanism of core–shell structures and some pioneering researchers have shown that energetic core–shell structures can be realized based on hydrogen bonding and π–π conjunction [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%